Socioeconomic Factors Influencing the Implementation of Good Agricultural Practices in Sustainable Vegetable Farming - Tilmiidzah Salma Fathin; Suswadi Suswadi (Global Health Science Group, 2026)
Good Agricultural Practices (GAP) is a certification-based farming standard intended to guarantee food safety, environmentally sound management, worker welfare, and product traceability, and its adoption is mandated for Indonesian horticultural producers under Law No. 13/2010 on Horticulture. Despite this mandate, uptake among smallholder vegetable farmers remains inconsistent, partly because many producers have not perceived a clear benefit from certification and are reluctant to renew it once obtained. This study aimed to determine the level of implementation of GAP standard operating procedures (SOP-GAP) among vegetable farmers in the Argoayuningtani Farmer Group, Selo Sub-district, Boyolali Regency, and to analyse the socioeconomic factors associated with that implementation. A quantitative descriptive study was conducted on 30 vegetable farmers in the Argoayuningtani Farmer Group, Boyolali, Indonesia. Data were collected via structured questionnaires and analyzed using descriptive statistics and Spearman’s rank correlation. Data were analysed using descriptive statistics and Spearman rank correlation. Implementation fell into the good category for land preparation, seed selection, fertilizer and pesticide provision, planting, and fertilizer application, and into the fair category for equipment use, plant maintenance, irrigation, pest and disease control, and harvesting. Farmers' age, education, land area, farming experience, livestock ownership, and income were significantly and positively correlated with SOP-GAP implementation across most components, whereas land-ownership status showed weak and largely non-significant associations. socioeconomic characteristics substantially shape the extent of GAP adoption among smallholder vegetable farmers. Strengthening farmer education, facilitating land access, and improving household income may accelerate the sustainability of GAP implementation in similar farming communities.